Status of Medical Records in a Tertiary Care Hospital - Happy Rani Barua; Mohammad Jalal Uddin; Maliha Ata; Himon Barua; Tanya Barua; Rozina Hoque (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Medical record, health record and medical chart often to refers to the comprehensive documentation of a patient's medical history and care within a spe cific healthcare provider's domain. A medical record encompasses various types of "notes" created over time by healthcare professionals, including observations, drug and therapy administration details, orders for treatments, test results, X-rays, and other reports.The aim of the study was to evaluate the status of Medical Record keeping among healthcare providers in a tertiary healthcare hospital service. Materials and methods: A retrospective observational study was conducted by recording data from secondary sources i.e. admission form, history sheet on admission, details recorded by nurses, progress sheets recorded by physicians, referral record sheets, reports of pathology, reports of radiology, informed consent form, operation notes, discharge certificates from the Record Department of Chattagram Maa-O-Shishu Hospital Medical College. The data were collected by data collectors after visiting the Record department and filling up a questionnaire after taking permission from the Record keeper on approval of Ethical Review Board of CMOSHMC. Record of the patients admitted to the indoor of various Departments were selected by systematic random sampling technique. Four days from the month of July and August 2024 were randomly selected and all the medical records of those days were used to fill up the questionnaire developed according to guidelines and frameworks provided by World Health Organization (WHO). Patients confidentiality was maintained. A total of 400 secondary data from the medical Record Department were selected to complete the questionnaire. Collected data was managed by a professional data manager. After completing the questionnaire the data were input into IBM SPSS (Version 24) and analyzed by frequencies and percentages. Results: Occupation of the patients were not recorded in the medical record. Name and signature of the receiving physicians was not recorded in 19.5% and 31% files. Family history was not recorded in 87 % medical records. 95% of files did not have differential diagnosis recorded in it. 80% files did not have informed consent collected from patients. Signature of surgeon were absent in the operation note. History of alcohol, smoking, sexual history, exercise, dietary habits were absent. The report of pathology was not preserved in the files. Diseases among relatives and causes of death of relatives were absent 95% medical records. 47% patients were discharged on request. Conclusion: Accurate recording of information in medical records can help prevent future litigations and medical negligence cases. Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 13-19